Do Zombies Rise when Interest Rates Fall? A Relationship Banking Model - Fabian Herweg; Maximilian Kähny (Center for Economic Studies and ifo Institute (CESifo), 2022)
An entrepreneur chooses a relationship bank or market finance. The advantage of bank finance is that the quality of the entrepreneur's project is identified early, allowing to liquidate low-quality projects. The loan contract induces an efficient continuation decision if the entrepreneur has sufficient wealth. If the entrepreneur is cash constrained, the loan contract is such that the bank continues inefficient projects, i.e., zombie lending occurs. In the short run - for a given contract - a drop in the market interest rate increases zombification. The bank adapts the contract to this drop in the long run, and zombification diminishes.
Keywords: D82; D86; G21; G33; 330; evergreening; interest rates; relationship banking; Zombie firms